PENINGKATAN PEMAHAMAN KONSEP MELALUI MODEL PEMBELAJARAN PICTORIAL RIDDLE PADA MATA PELAJARAN MEMPERBAIKI SISTEM REM SISWA KELAS X SMK NEGERI 1 SAWIT BOYOLALI TAHUN PELAJARAN 2014/2015 - Sadiyanto, Joko (Jurnal Nosel, 2015)
The objective of this research is to improve the conceptual understanding in the Brake System Repairing subject matter of the students in Grade X of the Light Vehicle Engineering Program of State Vocational High School 1 of Sawit, Boyolali. This Research used the Pictorial Riddle learning model are riddles presented to the class in picture or diagram form, depicting some novel or discrepant event. The validity of instrument was tested by using the content validity technique with the expert judgment and the application of Item and Test Analysis (Iteman 3.00). The instrument was exposed to the control class. The data of research used the descriptive comparative model of analysis. This research used classroom action research with two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. The result of reflection in the former cycle was made as a plan for the following cycle. The subjects of this research were the students as many as 30 in Grade X of Light Vehicle Engineering Program 3 of State Vocational High School 1 of Sawit, Boyolali in academic year 2014/2015. The result of research shows that the Pictorial Riddle learning model can improve the conceptual understanding in the Brake System Repairing subject matter as indicated by the result of evaluation test. The comparison between the students? average score of conceptual understanding in the pre-treatment and that of conceptual understanding in Cycle I shows that it improves from 59.67 to 76.55. The students? conceptual understandings from the pre-treatment to Cycle I and from Cycle I to Cycle II improve as much as 16.88% and 11.55% respectively with the class average score of 88.1. Thus, the application of the Pictorial Riddle inquiry learning model of can improve the conceptual understanding in the Brake System Repairing subject matter of the students in Grade X of Light Vehicle Engineering Program of State Vocational High School 1 of Sawit, Boyolali in academic year 2014/2015.